2009
DOI: 10.1136/bmj.b541
|View full text |Cite
|
Sign up to set email alerts
|

Information sheets for patients with acute chest pain: randomised controlled trial

Abstract: Objectives To determine whether providing an information sheet to patients with acute chest pain reduces anxiety, improves health related quality of life, improves satisfaction with care, or alters subsequent symptoms or actions.Design Single centre, non-blinded, randomised controlled trial.Setting Chest pain unit of an emergency department.Participants 700 consecutive patients with acute chest pain and no clear diagnosis at initial presentation.Interventions After a diagnostic assessment patients were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
1
25
1
1
Order By: Relevance
“…10,12 Thus, concentration of future research on the following 2 questions may be more important: (1) how to maximize the reassurance value of diagnostic tests and (2) whether reassurance should be targeted to particular patients. Three trials have reported that brief interventions to increase the acceptability of negative test results lead to improved reassurance, [42][43][44] and theoretical work supports this finding. 45 Targeting interventions (including reassurance and cognitive-based rehabilitation) to patients at higher risk of persistent symptoms is effective in patients with low back pain, 46 and diagnostic testing accompanied by enhanced explanation can be an appropriate strategy.…”
Section: Recommendations For Research and Practicementioning
confidence: 92%
“…10,12 Thus, concentration of future research on the following 2 questions may be more important: (1) how to maximize the reassurance value of diagnostic tests and (2) whether reassurance should be targeted to particular patients. Three trials have reported that brief interventions to increase the acceptability of negative test results lead to improved reassurance, [42][43][44] and theoretical work supports this finding. 45 Targeting interventions (including reassurance and cognitive-based rehabilitation) to patients at higher risk of persistent symptoms is effective in patients with low back pain, 46 and diagnostic testing accompanied by enhanced explanation can be an appropriate strategy.…”
Section: Recommendations For Research and Practicementioning
confidence: 92%
“…The content of previous successful face-to-face CBT interventions for NCCP (Esler et al, 2003; Jonsbu, Dammen, Morken, Moum, & Martinsen, 2011; Potts, Lewin, Fox, & Johnstone, 1999; van Peski-Oosterbaan et al, 1999) was also used to guide development. The intervention built on a prior information only leaflet (Arnold et al, 2009), with the inclusion of techniques to target anxiety. The intervention booklet comprised three sections:…”
Section: Methodsmentioning
confidence: 99%
“…Such materials have been effective for anxiety disorders (Lewis, Pearce, & Bisson, 2012) and may be particularly useful within this setting (Esler et al, 2003). Brief information leaflets for chest pain patients within the ED have been shown to have an effect on psychological outcomes but no impact on chest pain (Arnold, Goodacre, Bath, & Price, 2009). The need for brief interventions that impact on both psychological and physical outcomes is apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Entsprechend sollten Überlegungen angestellt werden, wie Interventionen dieser Art besser in die Routineversorgung integriert werden können. Auch vorherige Studien [Mayou et al, 1999;Sanders et al, 1997] [Arnold et al, 2009].…”
Section: Disclosure Statementunclassified